Calcification of vascular smooth muscle cells is induced by secondary calciprotein particles and enhanced by tumor necrosis factor-α. (August 2016) - Aghagolzadeh, Parisa; Bachtler, Matthias; Bijarnia, Rakesh; Jackson, Christopher; Smith, Edward R.; Odermatt, Alex; Radpour, Ramin; Pasch, Andreas
Abstract: Background and aims: Vascular calcification is prevalent in clinical states characterized by low-grade chronic inflammation, such as chronic kidney disease (CKD). Calciprotein particles (CPP) are calcium phosphate-containing nano-aggregates, which have been found in the blood of CKD patients and appear pro-inflammatory in vitro . The interplay of CPPs and inflammatory cytokines with regard to the calcification of vascular smooth muscle cells (VSMC), in vitro, has not been investigated yet. Methods: Primary or secondary CPP were generated using phosphate-enriched culture medium (DMEM/10% FBS) incubated at 37 °C. Human VSMC were cultured with these media and mineralization was measured. Expression of TNF-α was detected by qPCR, ELISA and Western blot in calcified VSMC. To further characterize the significance of TNF-α and its receptors for the calcification of VSMC, RNA interference experiments using siTNF-α, siTNFR1 and siTNFR2 were performed. Results: The addition of phosphate to cell culture medium containing DMEM/10% FBS led to the rapid formation of primary CPP, which underwent spontaneous transformation to secondary CPP. Exposure of VSMC towards secondary CPP led to pronounced and concentration-dependent calcification, whereas exposure towards primary CPP did not. Importantly, secondary CPP induced oxidative stress, and led to the up-regulation and release of TNF-α. Addition of TNF-α to the cell culture medium enhanced, whereas the suppression of endogenous TNF-α or TNF receptor type 1 (TNFR1) expression by siRNA, ameliorated calcification. Conclusions: Secondary, but not primary CPP, induce VSMC calcification. Secondary CPP induce the expression and release of TNF-α, which enhances calcification via its receptor TNFR1. Highlights: CPP spontaneously form when cell culture medium is supplemented with the high phosphate and calcium. Secondary CPP induce VSMC calcification in vitro, whereas primary do not. Secondary CPP induce the expression and release of TNF-α, which enhances calcification via its TNFR1 receptor.